The absence of HPV DNA in genital specimens from infants. Issue 4 (August 1993) - Chen, S; Slavin, J; Fairley, C K; Tabrizi, S N; Borg, A J; Billson, V; Garland, S M
Abstract : OBJECTIVE--To identify the prevalence of HPV DNA using the polymerase chain reaction (PCR) in neonatal foreskin and cervical specimens obtained at necropsy. MATERIALS--Foreskin and cervical specimens were obtained from consecutive neonates who had autopsies performed at The Royal Women's Hospital, Melbourne, from June 1991 to February 1992. Specimens were analysed for HPV DNA using the polymerase chain reaction and the L1 consensus primers and generic probes. RESULTS--Specimens were obtained from 98 neonates, 52 males and 46 female. The mean gestational age of the neonates was 29 weeks (range 20-42). Eighty neonates died in utero, three during labour and 15 following delivery. Ninety four were delivered vaginally whilst four were delivered by caesarean section. Samples were collected a mean of 20 hours (range 2-48) from the time of delivery. In 30 cases there was evidence of autolytic change while in the remaining cases, the histology was well preserved. No evidence of HPV DNA was found in any of the samples using the L1 general primers (95% confidence interval 0-3.6%). Recent cervical cytology was available on 70 of the infant's mothers. Six had cytological evidence of HPV infection while the remainder were normal. CONCLUSIONS--HPV DNA is uncommonly detected (by PCR) in foreskin and cervical specimens obtained from neonates.